Will there be blood? Incentives and substitution effects in pro-social behavior - Nicola Lacetera; Mario Macis; Robert Slonim (Institute for the Study of Labor (IZA), 2009)
We examine how economic incentives affect pro-social behavior through the analysis of a unique dataset with information on more than 14,000 American Red Cross blood drives. Our findings are consistent with blood donors responding to incentives in a standard way; offering donors economic incentives significantly increases turnout and blood units collected, and more so the greater the incentive's monetary value. In addition, there is no disproportionate increase in donors who come to a drive but are ineligible to donate when incentives are offered. Further evidence from a small-scale field experiment corroborates these findings and confirms that donors are motivated by the economic value of the items offered. We also find that a substantial fraction of the increase in donations due to incentives may be explained by donors substituting away from neighboring drives toward drives where rewards are offered, and the likelihood of this substitution is higher the higher the monetary value of the incentive offered and if neighboring drives do not offer incentives. Thus, extrinsic incentives motivate pro-social behavior, but unless substitution effects are also considered, the effect of incentives may be overestimated.
Keywords: D12; D64; I18; 330; Incentives; altruism; public good provision; pro-social behavior; public health; Soziales Verhalten; Altruismus; Ökonomischer Anreiz; Blutspende; Motivation; Substitutionseffekt; USA